Corn silk extract improves cholesterol metabolism in C57BL/6J mouse fed high-fat diets - Cha, Jae Hoon; Kim, Sun Rim; Kang, Hyun Joong; Kim, Myung Hwan; Ha, Ae Wha; Kim, Woo Kyoung (Nutrition research and practice, 2016)
Corn silk (CS) extract contains large amounts of maysin, which is a major flavonoid in CS. However, studies regarding the effect of CS extract on cholesterol metabolism is limited. Therefore, the purpose of this study was to determine the effect of CS extract on cholesterol metabolism in C57BL/6J mouse fed high-fat diets. Normal-fat group fed 7% fat diet, high-fat (HF) group fed 25% fat diet, and high-fat with corn silk (HFCS) group were orally administered CS extract (100 mg/kg body weight) daily. Serum and hepatic levels of total lipids, triglycerides, and total cholesterol as well as serum free fatty acid, glucose, and insulin levels were determined. The mRNA expression levels of acyl-CoA: cholesterol acyltransferase (ACAT), cholesterol 7-alpha hydroxylase (CYP7A1), farnesoid X receptor (FXR), lecithin cholesterol acyltransferase (LCAT), low-density lipoprotein receptor, 3-hyroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase), adiponectin, leptin, and tumor necrosis factor α were determined. Oral administration of CS extract with HF improved serum glucose and insulin levels as well as attenuated HF-induced fatty liver. CS extracts significantly elevated mRNA expression levels of adipocytokines and reduced mRNA expression levels of HMG-CoA reductase, ACAT, and FXR. The mRNA expression levels of CYP7A1 and LCAT between the HF group and HFCS group were not statistically different. CS extract supplementation with a high-fat diet improves levels of adipocytokine secretion and glucose homeostasis. CS extract is also effective in decreasing the regulatory pool of hepatic cholesterol, in line with decreased blood and hepatic levels of cholesterol though modulation of mRNA expression levels of HMG-CoA reductase, ACAT, and FXR.